Comparison of oregano essential oil as antibiotic or probiotic alterative in broilers̓ diet: Use of technique for order of reference by similarity to ideal solution - Hosseini, Seyed Abdollah; Hajati, Hosna; Alizadeh-Ghamsari, Amir Hossein; Lotfollahian , Houshang (Acta Scientiarum. Animal Sciences, 2025)
Antibiotic resistance is a major problem for public health worldwide, and nutritionists are searching for antibiotic alternatives. Oregano essential oil is one of the natural products that has antioxidant and antibacterial substances. In the present study the technique of ordering the preference by similarity to the ideal solution was applied to compare different feed additives regarding the biological parameters of broilers fed diets containing antibiotic, probiotic or different levels of oregano essential oil. A total of five hundred Arian broiler chicks were used in a completely randomized design with 5 treatments and 5 replicates. The experimental treatments were: 1) basal diet (control), 2) basal diet+150 ppm antibiotic Avilamycin, 3) basal diet +100 ppm probiotic Protexin, 4) basal diet+200 ppm oregano essential oil, 5) basal diet+400 ppm oregano essential oil. After obtaining data on performance, production index, heterophil to lymphocyte ratio, and ileum microflora of broilers, the multiple attribute decision making (MADM), and the technique for order of preference by similarity to ideal solution (TOPSIS) was applied. Results indicated that oregano essential oil had the potential to be considered as a natural probiotic or antibiotic replacement in broiler chickens̓ diet. Oregano essential oil improved FCR, production index, intestinal villus height/crypt depth of the broilers. Also, it decreased the bacterial count of E.Coli in the ileum content of the broilers. It conclusion using oregano essential oil at the level of 200 or 400 ppm of diet can be considered as probiotic or antibiotic natural alternative in broilers diet.